Recording and Simulating Proton-Related Metabolism in Bacterial Cell Suspensions - Cypionka, Heribert; Reese, Jan-Ole (Frontiers in Microbiology, 2021)
Proton release and uptake induced by metabolic activities were measured in non-buffered cell suspensions by means of a pH electrode. Recorded data were used for simulating substrate turnover rates by means of a new freeware app (proton.exe). The program applies Michaelis-Menten or first-order kinetics to the metabolic processes and allows for parametrization of simultaneously ongoing processes. The simulation includes changes of the transmembrane ΔpH, membrane potential and ATP gains, and might be helpful for understanding chemiosmotic energy conservation. In our experiments, the versatile sulfate-reducing bacterium Desulfovibrio desulfuricans CSN (DSM 9104) was used as model organism. We analysed sulfate uptake by proton-sulfate symport, scalar alkalinisation by sulfate reduction to sulfide, as well as nitrate and nitrite reduction to ammonia, and electron transport-coupled proton translocation. Two types of experiments were performed: In oxidant pulse experiments, cells were kept under H2, and micromolar amounts of sulfate, nitrate or nitrite were added. For reductant pulse experiments, small amounts of H2-saturated KCl were added to cells incubated under N2 with an excess of one of the above-mentioned electron acceptors. To study electron-transport driven proton translocation, the membrane potential was neutralised by addition of KSCN (100 mM). H+/e- ratios of electron-transport driven proton translocation were calculated by simulation with proton.exe. This method gave lower but more realistic values than logarithmic extrapolation. We could verify the kinetic simulation parameters found with proton.exe using series of increasing additions of the reactants. Our approach allows for studying a broad variety of proton-related metabolic activities at micromolar concentrations and time scales of seconds to minutes.